EFFORTS TO PREVENT ADOLESCENT REPRODUCTIVE HEALTH PROBLEMS THROUGH GAME-BASED PEER EDUCATOR TRAINING FOR ADOLESCENTS IN GEDOG WETAN VILLAGE - Mas’udah, Mas’udah; Sheilla Tania Marcelina; Astutik, Heny; Setyarini, Didien Ika (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
Adolescence is a critical transition stage to adulthood. Reproductive health issues such as early marriage and stunting are still a challenge. This activity aims to empower adolescents through peer educator training and the formation of peer tutors for skills related to becoming peer educators on reproductive health and maturation of marriage age in Gedog Wetan Village, Turen District, Malang Regency. The empowerment model used is the Locality Development Model, which involves the active participation of local communities, namely adolescents. The empowerment method uses Participatory Rural Appraisal and group discussions, role-play, demonstrations, training, mentoring, and evaluation. The number of adolescents involved in the training were male and female adolescents aged 15-19 years, totaling 25 people. The instrument used was an observation sheet to assess the skills of peer educators in providing education. The program implementation was carried out for 4 days, including training and mentoring. The training material includes peer educator material, reproductive health in adolescents, and maturation of marriage age, followed by demonstrations and simulations of educational media (educational games), demonstrations, and re-demonstrations on how to conduct health counseling to adolescents using media made by the service team. The results of the activity showed that the results of observations of the skills in conducting peer educators showed that most of the trainees were considered “competent” in providing education, especially in aspects such as the selection of topics and educational media, the ability to deliver material, the ability to provide opportunities to ask questions, motivational skills (inviting participants to interact with each other), and skills in conducting evaluations. The formation of peer tutor groups is an indicator of success in empowering adolescents as agents of change.